Question
upstudy study bank question image url

27. \( \frac{15^{7} \times 8^{6}}{5^{6} \times 24} \) 28. \( \frac{2^{2005} \times 5^{2000}}{100^{1000}} \) 29. \( \frac{7^{2 x}-1}{3 \times 7^{x}+3} \) 30. \( \frac{16^{x}-1}{5 \times 4^{x}-5} \) 31. \( \frac{25^{x}-4}{2 \times 5^{x}-4} \) 32. \( \frac{9^{x}-3^{x}-2}{6^{x}-2^{x+1}} \)

Ask by Marsh Weber. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

27. \( 3^6 \times 5 \times 2^{15} \) 28. 32 29. \( \frac{7^x - 1}{3} \) 30. \( \frac{4^x + 1}{5} \) 31. \( \frac{5^x + 2}{2} \) 32. \( \frac{3^x + 1}{2^x} \)

Solution

Below are the step‐by‐step simplifications: 27. Simplify (15⁷ × 8⁶)/(5⁶ × 24).  • Write 15 and 8 as products of primes:   – 15 = 3·5, so 15⁷ = 3⁷ × 5⁷.   – 8 = 2³, so 8⁶ = (2³)⁶ = 2¹⁸.  • Factor the denominator:   – 24 = 3 × 8 = 3 × 2³, so 5⁶ × 24 = 5⁶ × 3 × 2³.  • Thus,    (15⁷ × 8⁶)/(5⁶ × 24) = (3⁷ × 5⁷ × 2¹⁸)/(5⁶ × 3 × 2³)  • Cancel common factors:   – For 3: 3⁷/3 = 3⁶.   – For 5: 5⁷/5⁶ = 5.   – For 2: 2¹⁸/2³ = 2¹⁵.  • The simplified expression is 3⁶ × 5 × 2¹⁵. 28. Simplify (2^2005 × 5^2000)/(100^1000).  • Rewrite 100 as 10². Then 100^1000 = (10²)^1000 = 10²⁰⁰0.  • Since 10 = 2×5, we have 10²⁰⁰0 = 2²⁰⁰0 × 5²⁰⁰0.  • Now,   (2^2005 × 5^2000)/(2^2000 × 5^2000) = 2^(2005–2000)= 2⁵ = 32. 29. Simplify (7^(2x) – 1)/(3×7^x + 3).  • Notice the numerator is a difference of squares: 7^(2x) – 1 = (7^x – 1)(7^x + 1).  • Factor the denominator: 3×7^x + 3 = 3(7^x + 1).  • Cancel the common factor (7^x + 1) (assuming 7^x ≠ –1):   Result = (7^x – 1)/3. 30. Simplify (16^x – 1)/(5×4^x – 5).  • Write 16^x in terms of 4^x: 16^x = (4²)^x = 4^(2x). Then numerator = 4^(2x) – 1.  • Recognize the difference of squares: 4^(2x) – 1 = (4^x – 1)(4^x + 1).  • Factor the denominator: 5×4^x – 5 = 5(4^x – 1).  • Cancel (4^x – 1) (provided 4^x ≠ 1):   Result = (4^x + 1)/5. 31. Simplify (25^x – 4)/(2×5^x – 4).  • Write 25^x as (5²)^x = 5^(2x). So numerator = 5^(2x) – 4.  • Notice that 5^(2x) – 4 is a difference of squares: 5^(2x) – 4 = (5^x)² – 2² = (5^x – 2)(5^x + 2).  • Factor the denominator: 2×5^x – 4 = 2(5^x – 2).  • Cancel the common factor (5^x – 2) (assuming 5^x ≠ 2):   Result = (5^x + 2)/2. 32. Simplify (9^x – 3^x – 2)/(6^x – 2^(x+1)).  • Express all terms in prime bases:   – 9^x = (3²)^x = 3^(2x).   – 6^x = (2×3)^x = 2^x×3^x.   – 2^(x+1) = 2×2^x.  • Rewrite the numerator with t = 3^x:   – Numerator becomes t² – t – 2, which factors as (t – 2)(t + 1); that is, (3^x – 2)(3^x + 1).  • Rewrite the denominator:   – Denom = 2^x×3^x – 2×2^x = 2^x(3^x – 2).  • Cancel (3^x – 2) (assuming 3^x ≠ 2):   Result = (3^x + 1)/(2^x). These are the simplified forms for problems 27–32.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

The problems you’ve presented are great for illustrating how exponents, factoring, and simplification can be applied in mathematics. For instance, with expressions like \(\frac{15^{7} \times 8^{6}}{5^{6} \times 24}\), one can simplify first by breaking down the components into their prime factors for easier calculation—a nifty skill to save time and frustration! As for real-world applications, understanding these expressions often comes in handy in fields such as finance and science. For instance, when calculating compound interest, the use of exponentiation comes into play. Similarly, physics equations often use exponents to describe exponential decay or growth, so mastering these problems translates directly into skills useful in everyday problem-solving scenarios!

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy